Simplification of Boolean Expressions:
Boolean Expressions are simplified using following two methods:
1) Using Laws of Boolean algebra
2) Using K-Maps
Boolean Expressions are simplified using following two methods:
1) Using Laws of Boolean algebra
2) Using K-Maps
Simplification using Laws of boolean algebra:
This method is used by keeping few points in mind:
a) Take common from all min/ Maxterms in a way that any of the min/ Maxterms is left with 1, so that we can apply property of 1.
Let us understand by this example,
F(A,B,C) = AB'C + AB'+ AB'C'
taking AB' as common,
= AB'( C + 1 + C' ) (Distributive Law)
now using property of 1 which states that OR of 1 with any input results in 1, we will get the expression as = AB'(1) (Property of 1)
= AB' (Property of 1)
b) Take common from 2 min/ Maxterms in a way that both of the min/ Maxterms are left with single and opposite inputs. Let us take an example.
F(A,B,C) = AB'C + A'B'C'+ AB'C'+ABC
= AB'C + ABC+ A'B'C'+AB'C' (Commutative Law)
taking common in a way that 2 minterms have single and opposite inputs left
= AC( B' + B )+ B'C'( A'+A ) (Distributive Law)
= AC( 1 )+ B'C'( 1 ) (Complementarity Law)
= AC + B'C' (Property of 1)
c) Take common from 2 min/ Maxterms in a way that both of the min/ Maxterms are left with unequal inputs. Let us take an example.
F(A,B,C) = AB'C + AB+ A'BC' + A'B'C'
taking common in above mentioned way
= A(B'C+B)+ A'C'(B+B') (Distributive Law)
= A(B'+B)(C+B)+ A'C'(1) (Distributive Law)
= A(1)(C+B)+ A'C' (Complementarity Law)
= A(C+B)+ A'C' (Property of 1)
= AC+AB+ A'C' (Property of 1)
d) If there are 3 minterms having 2 inputs each and nothing is common then those minterms which have 1 input having both assertion and negation form will remain while 3rd term will be reduced by converting it to canonical form. Let us take an example.
F(A,B,C) = AB+BC+A'C
since input A has both assertion and negation form, we will convert the term which does not have input A, i.e. BC to its canonical form.
F(A,B,C) = AB+BC+A'C
= AB+BC.1+A'C (Property of 1)
= AB+BC(A+A')+A'C (Complementarity Law)
= AB+ABC+A'BC+A'C (Distributive Law)
= AB(1+C)+A'C(B+1) (Distributive Law)
= AB(1)+A'C(1) (Property of 1)
= AB+A'C (Property of 1)
No comments:
Post a Comment